Pengaruh Manajemen Kelas dan Manajemen Diri Terhadap Motivasi Belajar Siswa di SMPN 1 Jabiren Raya - Fernando Dorothius Pongoh (Jurnal Ilmiah Profesi Pendidikan, 2024)
Motivation is one of the mandatory requirements in learning activities, where learning motivation is one of the factors that can have an influence on a person's learning success. Classroom management can be used as an external factor that increases learning motivation, where an emotional condition of students is influenced by the classroom atmosphere. In addition, well-managed self-management will be a stimulant for yourself in learning that can increase learning motivation. The purpose of the study was to determine the effect of Classroom Management by teachers and student Self-Management on student Learning Motivation. The sample is selected students using the cluster sampling method, where grade VIII and IX students are used as cluster data so that a sample of 32 students is obtained. This study uses an associative quantitative approach, namely research to determine the influence between several variables, using multiple linear regression analysis. The results showed that classroom management managed by teachers and self-management by students themselves had a joint influence on student learning motivation in schools where the percentage of diversity was obtained at 46.5%.